Assessment of transportation efficiency for the delivery of construction material in North-Central Nigeria - Alumbugu, Polycarp; Shakantu, Winston; Tsado, Abel (Acta Structilia, 2020)
In Nigeria, knowledge on the management of construction material logistics system, especially in transportation, is inadequate. This article assesses construction material manufacturers’ transportation efficiency for the delivery of construction material, in order to improve manufacturers’ transport operation in North-Central Nigeria. A total of 32 construction material manufacturers delivered their material to 42 distribution centres/warehouses and retailer stores, and 30 construction sites were purposely selected. The selected construction materials manufacturers produce six types of materials, namely cement, reinforcement bars (steel), ceramic tiles, crushed stones, masonry hollow sandcrete blocks, and sand (fine and coarse). A case study research design method was used, in which quantitative data were collected and analysed. An observation (quantitative) guide was used as the research instrument. The quantitative data collected were analysed, using descriptive statistical tools such as frequencies and percentiles. The results revealed that transportation efficiency levels are low in their vehicles’ dwell time, loading and off-loading vehicles at the warehouses, retailer stores, and construction sites. It was also revealed that no technology was used in the transport system to integrate the manufacturers’ warehouses with the other logistics partners in the supply chain. The article concludes that manufacturers should address transportation operations along the delivery nodes to help ensure that the construction material arrives at its final destination at optimal quality, time and cost.